Fatherhood Da’wah Through Visual Images: A Multimodal Analysis of Instagram Da’wah Content on @abun_nada - Mega Satria Nurul Falah; Agus Darwanto; Syafa Maulida Kamila; Awaliyah Ainun Niswah (Insaniyat: Journal of Islam and Humanities, 2026)
This study examines the representation of fatherhood in visual da’wah content on social media, which plays an important role in shaping religious understanding and parenting practices within Muslim families. Situated within the fields of digital da’wah and Islamic communication, this study aims to analyze how fatherhood discourse is constructed through illustrative content on the Instagram account @abun_nada and to examine the role of visual, verbal, and layout elements in articulating Islamic moral teachings such as compassion, responsibility, and moral exemplarity. Employing a qualitative approach, this study applies multimodal discourse analysis to 24 purposively selected visual da’wah posts published on the Instagram account @abun_nada between November 2024 and November 2025. The posts were selected based on recurring fatherhood themes, father-child representations, and the integration of visual and verbal elements relevant to multimodal analysis. The findings indicate that the father figure is represented not as a hierarchical authority, but as a relational figure who constructs authority through caregiving actions, dialogic interaction presented through captions and direct speech, and emotional involvement represented through intimate visual framing and everyday interactions with children. These multimodal elements enable moral and religious meanings to be communicated implicitly, allowing da’wah to operate as a lived moral practice embedded in everyday experience. This study contributes to the development of digital da’wah and multimodal communication studies by demonstrating how Islamic parenting values and fatherhood norms are negotiated through relational representations on social media.